A possibility to improve the physical fatigue after artificial high concentration CO2 hot water immersion in athletes - Wada, T.; Hyodo, H.; Hirano, T.; Kashiwagi, Y.; Shintaku, Y.; Yamamoto, N. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The bathing and sleep processes in physical recovery play an important role in athletes. One of the body recovery is the night sleep. The hot spring water containing high concentration carbon dioxide (CO2 =1000 ppm) has long been applied to the patients suffering from cardiovascular diseases in balneotherapy. The purpose of this study is to examine the physical recovery after artificial high concentration CO2-water immersion in athletes.